PERBANDINGAN STRUKTUR RANGKA BATANG STATIS TERTENTU MENGGUNAKAN METODE MEKANIKA KLASIK DAN PROGRAM (SAP 2000) - Dwi Deshariyanto; Anita Intan Nura Diana; Subaidillah Fansuri (Fakultas Teknik, Universitas Wiraraja, 2022)
use of computers in the completion of construction planning requires reliable and accurate human resources in operating computerized civil engineering. The classical engineering mechanics method is a relatively simple and effective way to teach the basics of engineering mechanics and to train the engineering intuition or engineering judgment needed to evaluate the results of advanced computer programs. The aim of the study was to determine the magnitude of the reactions and forces as well as the magnitude of the difference between the reactions and forces in certain static truss structures using classical mechanics methods and programs (SAP 2000). The design of this study compares the classical mechanics method using the node point method with the SAP 2000 program for certain static truss structures which include roof trusses and bridge trusses. The data of this study were carried out by frequency analysis and t test analysis. Completion of certain static structures with roof and bridge models using the manual method with the program (SAP) 2000 resulted in differences in the magnitudes of the forces in the rods, these differences were due to differences in the level of accuracy. The truss structure of the roof and bridge models under certain static conditions produces the magnitude of the forces in the trunk with the same variance and there is no difference between the average magnitudes of the resulting forces.